The handbook of interior design - Thompson, Jo Ann Asher, 1948-; Blossom, Nancy H. (2015)
"The Handbook of Interior Design offers a compilation of current ways of thinking that inform the discipline of interior design"--
Machine generated contents note: Section 1: Introduction: The Shaping of Interior Design Section 2: Explorations of the History of Interior Design Chapter 1: An Overview of Phenomenology for the Design Disciplines David Wang Chapter 2: Dorothy Draper and the American Housewife: A Study of Class Values and Success John Turpin Chapter 3: The Political Interior Mary Ann Beecher Chapter 4: Taylorizing the Modern Interior Ronn Daniel Chapter 5: Bringing the Past In: Narrative Inquiry and the Preservation of Historic Interiors Erin Cunningham Section 3: Perspectives of the Practice of Interior Design Chapter 6: Aesthetic Coding in Interior Design Mads Nygaard Folkmann Chapter 7: Toward a Creative Ecology of Workplace Design Margaret Portillo and Jason Meneely Chapter 8: Designing Emotional Connection into the Workplace: A Story of Authentic Leadership Sheila Danko Chapter 9 Exploring the Schism: Toward an Empathetic Language Shauna Corry Chapter 10: Ways of Knowing: a Position on the Culture of Interior Design Practice Janice Barnes Chapter 11: Sustainable, Life span Design, a New Model Amber Joplin Chapter 12: Frameworks for Decision making in Design for the Aging Halime Demarkin Chapter 13: Designing More Successful Social Spaces: Lessons Learned from a Continuing Care Retirement Community Study Nichole M. Campbell Chapter 14: Developing a Person Centric Design Philosophy Jill Pable Chapter 15: In Support of Contemporary Identity: the Modern Palestinian Home May Sayrafi Chapter 16: Creativity in Interior design: Cross-cultural Practitioners' Reviews of Entry-level Portfolios Siriporn Kobnithikulwong Chapter 17: Human Responses to Water Elements in Interior Environments: A Culture and Gender Comparison Gwo Fang Lin Chapter 18: Concerns with Daylight and Health Outcomes Michael Kroelinger Chapter 19: Healthy Interiors for the Visually Impaired Dak Kopec Chapter 20: Interior People Places: The Impact of the Built Environment on the Third Place Experience Dana Vaux Chapter 21: Places in the Virtual and Physical Continuum: Examining the Impact of Virtual Behaviors on Place Attributes of Wireless Coffee Shops Newton D'SLuouza, Yu-Fong Lin Chapter 22: The Relationship between Historic Preservation and Sustainability in Interior Design Lisa Tucker Chapter 23: Forging Empathetic Connections to Create Compatible Designs in Historic Buildings Jessica Goldsmith Section 4: Considerations of Education in Interior Design Chapter 24: The Phenomenological Contribution to Interior-Design Education and Research: Place, Environmental Embodiment, and Architectural Sustenance David Seamon Chapter 25: Testing a Culture-Based Design Pedagogy, a Case Study Abi Asojo Chapter 26: Connecting the Scholarship of Teaching and Learning to the Discipline of Interior Design Isil Oygur and Bryan Orthel Chapter 27: Engaging Voices within a Dynamic Problem-based Learning Context Tiiu Poldma Chapter 28: Aesthetic Theory and Interior Design Pedagogy Ji Young Cho and Benyamin Schwarz Chapter 29: Interior Design Teaching and Learning in Elementary and Secondary Education (K-12) Stephanie A. Clemons Chapter 30: Community Building through Interior Design Education Patrick Lucas Chapter 30: A Reflective Journey in Teaching Interior Design: The Virtual Studio Kathleen Gibson .
Includes bibliographical references and index.
Keywords: Interior architecture; Interior architecture -- Philosophy; Interior decoration; Interior decoration -- Philosophy; ARCHITECTURE / Interior Design / General